wyrażenia algebraiczne sprawdź czy umiesz

Odpowiedź:
3. a) [tex]3a + 2a * 5a-7a^{2} +\frac{6a^{2} }{3} = 3a + 10a^{2} - 7a^{2} + 2a^{2}= 3a+3a^{2}+2a^{2}= 3a + 5a^{2}[/tex]
b) [tex]3x^{2} + 2x * (-3x) + 4x^{2} + \frac{15x}{3} = 3x^{2} -6x^{2} +4x^{2} +5x=-3x^{2} +4x^{2} +5x=x^{2} +5x[/tex]
c)[tex]-4y*5x+2x*5-3x*2y+\frac{8xy}{2}=-20xy+10x-6xy+4xy=-20xy+10x-2xy=-22xy+10x[/tex]
d)[tex]\frac{10ab}{5}+5b^{2} -2b*5b-3b^{2}*2-2ab=2ab+5b^{2}-10b^{2}-6b^{2} -2ab=-11b^{2}[/tex]
4. skreślić:
a) 9a - (3a-3b)
2a - (3b +4a)
b) 2p(2p+3r)
2 * 3pr + 2p * 2p
c) 8xy * 3x
9y * 2x
2x * 3y * 3y
5. a)[tex](x+7)(y-2) =xy-2x+7y-14[/tex]
b)[tex](2a-3)(5-b)=10a-2ab-15+3b[/tex]
c)[tex](p-5)(t+3)=pt+3p-5t-15[/tex]
d)[tex](3s-2)(5s+1)=15s^{2} +3s-10s-2=15s^{2} -7s-2[/tex]
e) [tex](6-2x)(3x+1)=18x+6-6x^{2} -2x=16x+6-6x^{2}[/tex]
f) [tex](a+b)(2b-a)=2ab-2a^{2} +2b^{2} -ab=ab-2a^{2} +2b^{2}[/tex]
g) [tex](5x-3)(y-2)=5xy-10x-3y+6[/tex]
h)[tex](3p^{2} +t)(t^{2}-4p)=3p^{2}t^{2} -12p^{3}+t^{3}-4pt[/tex]